Interpreting Prefrontal Recruitment During Walking After Stroke: Influence of Individual Differences in Mobility and Cognitive Function - Chatterjee, Sudeshna A.; Fox, Emily J.; Daly, Janis J.; Rose, Dorian K.; Wu, Samuel S.; Christou, Evangelos A.; Hawkins, Kelly A.; Otzel, Dana M.; Butera, Katie A.; Skinner, Jared W.; Clark, David J. (Frontiers in Human Neuroscience, 2019)
Background: Functional near-infrared spectroscopy (fNIRS) is a valuable neuroimaging approach for studying cortical contributions to walking function. Recruitment of prefrontal cortex during walking has been a particular area of focus in the literature. The present study investigated whether task-related change in prefrontal recruitment measured by fNIRS is affected by individual differences in people post-stroke. The primary hypotheses were that poor mobility function would contribute to prefrontal over-recruitment during typical walking, and that poor cognitive function would contribute to a ceiling in prefrontal recruitment during dual-task walking (i.e., walking with a cognitive task). Methods: Thirty-three adults with chronic post-stroke hemiparesis performed three tasks: typical walking at preferred speed (Walk), serial-7 subtraction (Serial7), and walking combined with serial-7 subtraction (Dual-Task). Prefrontal recruitment was measured with fNIRS and quantified as the change in oxygenated hemoglobin concentration (ΔO2Hb) between resting and active periods for each task. Spatiotemporal gait parameters were measured on an electronic walkway. Stepwise regression was used to assess how prefrontal recruitment was affected by individual differences including age, sex, stroke region, injured hemisphere, stroke chronicity, 10 meter walking speed, balance confidence measured by Activities-specific Balance Confidence (ABC) Scale, sensorimotor impairment measured by Fugl-Meyer Assessment, and cognitive function measured by Mini-Mental State Exam (MMSE). Results: For Walk, poor balance confidence (ABC Scale score) significantly predicted greater prefrontal recruitment (ΔO2Hb; R2 = 0.25, p = 0.003). For Dual-Task poor cognitive function (MMSE score) significantly predicted lower prefrontal recruitment (ΔO2Hb; R2 = 0.25, p = 0.002). Conclusions: Poor mobility function predicted higher prefrontal recruitment during typical walking, consistent with compensatory over-recruitment. Poor cognitive function predicted lower prefrontal recruitment during dual-task walking, consistent with a recruitment ceiling effect. These findings indicate that interpretation of prefrontal recruitment should carefully consider the characteristics of the person and demands of the task.